Revisiting the NIH Taskforce on the Research needs of Eosinophil-Associated Diseases (RE-TREAD). Issue 1 (19th April 2018) - Khoury, Paneez; Akuthota, Praveen; Ackerman, Steven J; Arron, Joseph R; Bochner, Bruce S; Collins, Margaret H; Kahn, Jean-Emmanuel; Fulkerson, Patricia C; Gleich, Gerald J; Gopal-Srivastava, Rashmi; Jacobsen, Elizabeth A; Leiferman, Kristen M; et al.
Abstract: Eosinophil-associated diseases (EADs) are rare, heterogeneous disorders characterized by the presence of eosinophils in tissues and/or peripheral blood resulting in immunopathology. The heterogeneity of tissue involvement, lack of sufficient animal models, technical challenges in working with eosinophils, and lack of standardized histopathologic approaches have hampered progress in basic research. Additionally, clinical trials and drug development for rare EADs are limited by the lack of primary and surrogate endpoints, biomarkers, and validated patient-reported outcomes. Researchers with expertise in eosinophil biology and eosinophil-related diseases reviewed the state of current eosinophil research, resources, progress, and unmet needs in the field since the 2012 meeting of the NIH Taskforce on the Research of Eosinophil-Associated Diseases (TREAD). RE-TREAD focused on gaps in basic science, translational, and clinical research on eosinophils and eosinophil-related pathogenesis. Improved recapitulation of human eosinophil biology and pathogenesis in murine models was felt to be of importance. Characterization of eosinophil phenotypes, the role of eosinophil subsets in tissues, identification of biomarkers of eosinophil activation and tissue load, and a better understanding of the role of eosinophils in human disease were prioritized. Finally, an unmet need for tools for use in clinical trials was emphasized. Histopathologic scoring, patient- and clinician-reported outcomes, and appropriate coding were deemed of paramount importance for research collaborations, drug development, and approval by regulatory agencies. Further exploration of the eosinophil genome, epigenome, and proteome was also encouraged. Although progress has been made since 2012, unmet needs in eosinophil research remain a priority. Review on eosinophil biology and eosinophil-related disorders (2012–2017) with a focus on continued unmet needs in eosinophil-associated diseases.